L’EOE, l’Escòla Occitana d’Estiu, centre de formation associatif et ses fondateurs Marceau Esquieu, Christian Rapin et Jean Rigouste - Marie-Anne Châteaureynaud; Céline Piot (Lengas)
As part of the research conducted by the two authors on Occitanism in Aquitaine, this contribution focuses on the founders of the Occitan summer school (created in Lot-et-Garonne in 1974), who were fully aware of the urgency of teaching the Oc language: Marceau Esquieu, Jean Rigouste, Christian Rapin, who became true cultural actors in the Agenais. Developing an intermediate level between the school and university levels, this IEO-affiliated association offers workshops each year, makes resources available and creates teaching materials in order to train speakers and teach Occitan culture and literacy.